Levels of TNF‐α, soluble TNF receptors (sTNFR1, sTNFR2), and cognition in bipolar disorder. (27th March 2013) - Doganavsargil‐Baysal, Ozge; Cinemre, Buket; Aksoy, Umut Mert; Akbas, Halide; Metin, Ozmen; Fettahoglu, Cıgıl; Gokmen, Zehra; Davran, Fatih
Abstract : Objective: Tumor necrosis factor‐alpha (TNF‐α) may play an important role in bipolar disorder (BD) pathogenesis. There is only one study about a relationship between TNF‐α levels and cognitive impairments in BD. The aim of the present study was to see whether TNF‐α, soluble P55 TNF receptor (sTNFR1), and soluble P75 TNF receptor (sTNFR2) levels in BD patients are different from controls and to investigate the relationships between the levels of TNF‐α, sTNFR1, and sTNFR2 and the cognitive functions in euthymic BD patients and controls. Methods: We assessed 54 BD type I patients and 18 controls by using a battery of neuropsychological tests. Serum TNF‐α levels were measured using a commercially available enzyme‐linked immunosorbent assay, whereas serum sTNFR1 and sTNFR2 levels were measured using a commercially enzyme‐amplified sensitivity immunoassay kit. Results: We found that levels of sTNFR1 and sTNFR2 in BD patients were different from controls. No difference was detected between the BD group and the control group for levels of TNF‐α. TNF‐α level was found to have a negative correlation with the delayed recall in RAVLT. Conclusions: High levels of sTNFR1 and sTNFR2 in euthymic patients showed that it may support that proinflammatory process continues in euthymic period. This is the first study which showed increased sTNFR2 levels in euthymic period, which could be interpreted as a compensatory mechanism and again the first which deals with verbal memory. Copyright © 2013 John Wiley & Sons, Ltd.